Molecular analysis of spike branching observed in black pepper (piper nigrum L.) type from Idukki - Vimarsha H S (Department of Plant Biotechnology, College of Agriculture, 2009)
The study entitled “Molecular analysis of spike branching observed in black pepper (Piper nigrum L.) type from Idukki” was conducted at the Department of Plant Biotechnology, College of Agriculture, Vellayani, Thiruvananthapuram during 2006-2008. The objective of the study was to analyse the sequence homology for the inflorescence architecture gene (TFL1) and flowering gene (FT) in spike branching black pepper type from Idukki, using polymerase chain reaction technique.